Complexation of 5-Fluorouracil with β-Cyclodextrin and Sodium Dodecyl Sulfate: A Useful Tool for Encapsulating and Removing This Polluting Drug - Cabral, Ana M. T. D. P. V. (2022)
The formation of complexes of the drug 5-fluorouracil (5-FU) with β-cyclodextrin (β-CD) and sodium dodecyl sulphate (SDS) was studied through experimental measurements of the ternary mutual diffusion coefficients (D11, D22, D12, and D21) for the systems {5-FU (component 1) + β-CD (component 2) + water} and {5-FU (component 1) + SDS (component 2) + water} at 298.15 K and at concentrations up to 0.05 mol dm-3 by using the Taylor dispersion method, with the objective of removing this polluting drug from the residual systems in which it was present. The results found showed that a coupled diffusion of 5-FU occurred with both β-CD and SDS, as indicated by the nonzero values of the cross-diffusion coefficients, D12 and D21, as a consequence of the complex formation between 5-FU and the β-CD or SDS species. That is, 5-FU was solubilized (encapsulated) by both carriers, although to a greater extent with SDS (K = 20.0 (±0.5) mol-1 dm3) than with β-CD (K = 10.0 (±0.5) mol-1 dm3). Values of 0.107 and 0.190 were determined for the maximum fraction of 5-FU solubilized with β-CD and SDS (at concentrations above its CMC), respectively. This meant that SDS was more efficient at encapsulating and thus removing the 5-FU drug.